Ferromagnetic resonance of Ni wires fabricated on ferroelectric LiNbO3 substrate for studying magnetic anisotropy induced by the heterojunction - Akinobu Yamaguchi; Akiko Nakao; Takuo Ohkochi; Akira Yasui; Toyohiko Kinoshita; Yuichi Utsumi; Tsunemasa Saiki; Keisuke Yamada (AIP Advances, 2018)
The electrical ferromagnetic resonance of micro-scale Ni wires with magnetic anisotropy induced by the heterojunction between the Ni layer and ferroelectric single crystalline LiNbO3 substrate was demonstrated by using rectifying effect. The two resonance modes were observed in the Ni wire aligned parallel to the applied magnetic field in plane. The lower resonance frequency mode is considered to correspond to the normal resonance mode with domain resonance, while the higher resonance mode is attributed to the mode which is contributed by the heterojunction between the Ni layer and LiNbO3 substrate. Our results manifest that the rectifying electrical detections are very useful for understating and evaluating the magnetic properties induced by the heterojunction.